133 Cognitive Impairment Following Overdose on Lamotrigine. (15th June 2018) - Chandrashekar, Geetha; Ash, David; Singh, Garima
Abstract: Objective: To generate hypotheses, accumulate scientific data about rare presentations, and serve as a major educational tool. Method: This is a retrospective case report of a patient in inpatient unit. Introduction: Lamotrigine is a mood stabilizer with unique mechanisms of action. At therapeutic levels, it has been reported that Lamotrigine is neuroprotective and improves cognition. In this case, we present a patient who suffered significant cognitive slowing following overdose on Lamotrigine. Case: A 17yo white male with a diagnosis of Autism spectrum disorder and Bipolar disorder type 1 was admitted for bizarre behavior and profound cognitive impairment. His past psychiatric history was significant for two suicide attempts - first by overdose on baby aspirin and second by overdose on Lamotrigine, both of which had occurred about six months prior to his presentation and had each required an inpatient hospitalization. His family reported that since his overdose on Lamotrigine, he had been withdrawn, aloof, and appeared depressed. His school teachers had noticed significant decline in his memory, attention and concentration, and there had been noticeable impairment in his ability to follow commands or complete a task. On assessment, he was noted to have significant psychomotor slowing, latency in speech and thought blocking. At the time of his presentation, he was on Lithium 300mg BID. A careful review of his previous medical records revealed that he had been on a combination of Seroquel, Lamotrigine and Lithium prior to his overdose attempt on Lamotrigine. During this hospitalization, Seroquel was restarted. Patient tolerated the medication well. There were no safety concerns and he was deemed safe to discharge under 24hr supervision of his family. He has since been followed up in clinic. Although he continues to have some cognitive slowing, overall, he has demonstrated slow but steady improvement. Discussion: Lamotrigine acts by blocking voltage sensitive sodium channels. It also reduces release of glutamate, a major excitatory neurotransmitter in the central nervous system. Glutamate modulates synaptic plasticity, a property thought to be vital for memory and learning. While too much glutamate causes over activation of NMDA receptors resulting in increased intracellular oxidative stress and eventually apoptosis, too little glutamate may lead to decreased glutamate mediated postsynaptic excitation of neural cells and thus impacting memory formation, learning and cognition. At therapeutic levels (2.5- 15mcg/ml), it has been reported that Lamotrigine is neuroprotective and improves cognition. At the time of overdose, our patient had a Lamotrigine level of 21.5mcg/ml. There is limited literature on cognitive effect of supra-thrapeutic levels of Lamotrigine. As such, a causal relationship cannot be determined from a single care report. Also in differentials to consider are schizophrenia and seizures from lamotrigine withdrawal. Funding Acknowledgements: No funding.